PELAKSANAAN VAKSINASI TETANUS TOXOID PADA IBU-IBU DI DAERAH PEDESAAN - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1989)
A descriptive study on the obstacles of implementating Tetanus Toxoid Vaccination was carried out at Kecamatan Godean. Subjects were pregnant mothers who came at the Village Weighing Program during 1983. Questionnaires were used to collect data by directly interviewing 110 mothers. The results showed that mothers' knowledge of preventing Tetanus Neonatorum was good, but 89,09% didnot know when the vaccination had to be done. Forty six mothers didnot get any information about the vaccination when they were vaccinated.